The Development of Student Worksheets (LKPD) On Relationship and Functions for High School Students - Br.Ginting, Rania Idka Putri; Ammy, Putri Maisyarah (Holistic Science, 2022)
The purpose of this study was to determine the design for developing Student Worksheets on the subject of relations and functions for junior high school students. This research model is the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, Evaluation, but in this study the researchers limited it only to the development stage. (Development). The subjects of this study were six experts consisting of two mathematics education lecturers and one mathematics teacher as a material expert as well as two mathematics education lecturers and one mathematics teacher as a media expert. The research instrument used was a learning media questionnaire. Consists of a questionnaire of material experts and media experts. Based on data analysis, the average value obtained by material experts is 4.3 and media experts is 4.4. From these results, it can be stated that the mathematics learning media meets the validity requirements of the learning media with an overall average value of 4.3 including in the Very Good category. Thus, from the validation results it can be stated that the LKPD developed meets the validity requirements and is declare eligible